The Impact of Granting Building Use Rights to Foreign Citizens Living in Indonesia - Hanura Wijayanti, Mayday; Sudiro, Amad (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the legal implications of granting building use rights to foreign nationals under the Job Creation Law. The main problem that currently occurs is the limited availability of land in Indonesia, while development is progressing rapidly, especially in urban areas. To meet the needs of the community, including foreign citizens, for housing, the government then took the path of building flats as part of housing development, considering the limited land in urban areas. In its development, the government then enacted the Job Creation Law, which turned out to be inconsistent with previous regulations. This is interesting to study regarding the impact that will occur if Building Use Rights are granted to Foreign Citizens living in Indonesia, so that the problems that arise can be in the form of legal certainty of the Job Creation Law regarding ownership of Building Use Rights by Foreign Citizens and ownership of flat units by Foreign Citizens according to the Job Creation Law linked to the principle of nationality. This study uses a normative legal approach method by reviewing library materials or secondary data, and the nature of this research is descriptive and analytical. The results of the study concluded that the legal certainty of ownership of Apartment Ownership Rights on land with building use rights by foreigners based on the Job Creation Law is still not guaranteed, because in the UURS and UUPA, foreigners can only have usage rights, while in the UUCK, they can have HGB. The novelty of this study lies in its normative analysis of conflicting regulations and the identification of legal gaps in the implementation of foreign ownership of apartment units.